Beyond the Headlines: The Influence of Insurance Pest Management on an Unseen, Silent Entomological Majority - Krupke, Christian H.; Tooker, John F. (Frontiers in Sustainable Food Systems, 2020)
For most of the last two decades, insect pest management in key grain and oilseed crops has relied heavily on an insurance-based approach. This approach mandates a suite of management tactics prior to planting and in the absence of pest data. Because there is little flexibility for using these tactics individually, most producers have adopted this full suite of practices despite mounting evidence that some components do not provide consistent benefits. In North America in particular, this preventive approach to insect pest management has led to steep increases in use of neonicotinoid insecticides and subsequent increases in neonicotinoids in soil and water within crop fields and beyond. These increases have been accompanied by a host of non-target effects that have been most clearly studied in pollinators and insect natural enemies. Less attention has been given to the effects of this practice upon the many thousands of aquatic insect species that are often cryptic and offer negligible, or undefined, clear benefits to humans and their commerce. A survey of the literature reveals that the non-target effects of neonicotinoids upon these aquatic species are often as serious as for terrestrial species, and more difficult to address. By focusing upon charismatic insect species that provide clearly defined services, we are likely dramatically under-estimating the effects of neonicotinoids upon the wider environment. Given the mounting evidence base demonstrating that the pest management and crop yield benefits of this approach are negligible, we advocate for a return to largely-abandoned IPM principles as a readily accessible alternative path.